The effect of institutions on productivity spillovers from FDI to domestic firms: Evidence in Vietnam - Huynh Quoc Vu; Pham Thi Bich Ngoc; Nguyen Quyen Le Hoang Thuy To (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to investigate the impact of formal institutions and their components on productivity spillovers from FDI enterprises to domestic firms' TFP in developing countries like Vietnam. Design/methodology/approach: The study, conducted in two steps to explore the relationship, is to estimate the firm's TFP in accordance with the semi-parametric method of Levisohn and Petrin (2003). Regression is in accordance with the equation with panel data and adjusted by Driscoll and Kraay standard errors. An unbalanced panel data, related to more than 61,600 Vietnamese manufacturing firms from 2012 to 2017, is combined with the Provincial Institutional Quality Survey (PAPI index) and IO table. Findings: The local institutions have a positive impact on promoting learning ability and increasing productivity of domestic firms, especially small and medium enterprises (SMEs) that take better advantage of this effect. Vertical linkages with FDI enterprises assist local firms to increase productivity while horizontal linkages bring in negative effects. Domestic enterprises with high productivity (in the top 25%) receive positive spillover effects from horizontal linkages and vertical linkages and gain positive impacts of the institution on productivity whereas the group of low-productivity enterprises records negative impacts. This research highlights those enterprises operating in the region where institutions have transparency, accountability, participation in comments and effective corruption control can absorb spillovers and improve their productivity as well as the transparency and corruption control are recognized as having a positive impact through horizontal linkages. Research limitations/implications: With the limitation of research data being conducted only on manufacturing enterprises, there is a lack of data on the impact of service enterprises. The study only stops at understanding the impact of formal institutional effects on productivity spillovers whereas informal institutional effects will be studied in the future. Furthermore, the productivity spillovers of FDI enterprises are explored in general besides other FDI forms that will have different productivity spillovers like offshore. From the results of this study, the governments of developing countries should improve their institutions to encourage local enterprises to take the advantage of spillover effects from FDI enterprises as well as pay more attention to regional factors by supplementing development priority policies based on the capacity of each region. Institutional quality at provincial level has a positive impact on productivity spillovers; consequently, it is essential to have policies for further institutional improvement. Originality/value: This is the first research paper on the impact of the institutional factor at provincial level on firm's productivity in developing countries like Vietnam. Theoretically, the impact of formal institutions on spillover effects from FDI enterprises is also clarified. In addition, our findings have implications for local economic development policies: vertical linkages promote domestic firms to increase their productivity while horizontal linkages of FDI enterprises in the same industry generate adverse impacts. This paper suggests some feasible solutions for SMEs in developing countries towards their productivity improvement.
Keywords: 650; Institution region; Foreign direct invest; Spillover; Absorption; Total factor productivity